Upgrading municipal lagoons in temperate and cold climates: Total nitrogen removal and phosphorus assimilation at ultra‐low temperatures. (11th June 2021) - D'Aoust, Patrick M.; Vincent, Simon; LeBlond, Guillaume; Arabgol, Raheleh; Hérard, Richard; Ahmed, Warsama; Guilherme, Stéphanie; Kinsley, Chris; Delatolla, Robert
Abstract: In this study, a municipal lagoon with high wintertime effluent total ammonia nitrogen (TAN) concentrations was upgraded with a pilot‐scale nitrifying‐nitrifying‐denitrifying (NIT‐NIT‐DENIT) moving bed biofilm reactor (MBBR) treatment train to characterize its effluent over wintertime operation, investigate the feasibility of upgrading lagoons to achieve substantial biological total nitrogen removal across ultra‐low temperatures (0.6–3.0) and to investigate nitrification inhibition pathways in facultative lagoon systems at ultra‐low temperatures. Throughout the study, it was observed that the system substantially reduced total nitrogen (TN) and total phosphorus (TP) effluent concentrations by an average of 69.8 ± 24.5% and 74.7 ± 20.1%, respectively. Furthermore, it was observed that sulfide toxicity may play an important role in the inhibition of nitrifying organisms in lagoons. Finally, the MBBR treatment technology has emerged as a suitable and sustainable upgrade technology for existing lagoon and waste stabilization pond facilities operating in temperate, northern and cold climate countries.